2022
DOI: 10.1111/camh.12628
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents' problematic internet and smartphone use in (cyber)bullying experiences: A network analysis

Abstract: Background: This study investigates both offline and online bullying perpetration and victimization in association with problematic internet use (PIU) and problematic smartphone use (PSU), while also considering the related psychosocial difficulties. Methods: A total of 3939 adolescents (49.4% boys, aged 13-15 years) from a representative sample of schools in Slovakia was obtained from the Health Behavior in School-aged Children (HBSC) project in 2018. Due to the lack of similar complex research and the expect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Although these studies provide valuable insights on the structure of the network between PSU and different psychological constructs, most have focused on adolescents from specific cultural backgrounds. As far as we know, most of the existing research is conducted in developed countries with limited research conducted in East European countries (Blinka et al, 2023). This calls for an investigation of the interrelationships between PSU and mental health outcomes in diverse populations to inform future research.…”
Section: The Network Approach Of Psumentioning
confidence: 99%
“…Although these studies provide valuable insights on the structure of the network between PSU and different psychological constructs, most have focused on adolescents from specific cultural backgrounds. As far as we know, most of the existing research is conducted in developed countries with limited research conducted in East European countries (Blinka et al, 2023). This calls for an investigation of the interrelationships between PSU and mental health outcomes in diverse populations to inform future research.…”
Section: The Network Approach Of Psumentioning
confidence: 99%
“…As more powerful information technology is produced, the potential for cyberbullying and the misuse of information technology increases due to the immense power of virtual networks and Internet-based communication (Blinka et al, 2023). Researchers are debating its intrinsic susceptibility to various sorts of deviant misuse and inappropriate use more than before (Giumetti & Kowalski, 2022;Lee et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the potential of the PIU to bring about considerable psychological harm has been highlighted. Numerous studies have shown that PIU is associated with intensive negative outcomes, such as the impairment of functional connections related to emotional cognitive control and social brain networks ( Arató et al, 2023 ), self-injurious behavior, loneliness, hyperactivity, depressive symptoms, anxiety problems, social phobia sleep disturbances, reduced scholastic achievement, low self-esteem, poor family function, and less life satisfaction ( Arrivillaga, Rey, & Extremera, 2020 ; Blinka, Stašek, Šablatúrová, Ševčíková, & Husarova, 2023 ; Ciarrochi et al, 2016 ; Derbyshire et al, 2013 ; El Asam, Samara, & Terry, 2019 ; Ko et al, 2008 ; Lavoie et al, 2023 ; Stead & Bibby, 2017 ). Davis (2001) has defined two distinct types of PIU based on a theoretical cognitive and behavioral model, including generalized PIU and specific PIU.…”
Section: Introductionmentioning
confidence: 99%